KEMAMPUAN BERPIKIR KREATIF SISWA BERDASARKAN ADVERSITY QUOTIENT PADA MATERI DIMENSI DUA - Agus Widiyanto; Agung Hartoyo; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2021)
This study aims to obtain students' creative thinking skills based on Adversity Quotient intelligence on the flat shape material at SMK-SMTI Pontianak. The research method used is descriptive method with survey research form. The number of research subjects was 12 students of class XI SMK-SMTI Pontianak. The data collection tools used were a written test to determine the level of students 'mathematical creative thinking skills and an Adversity Quotient questionnaire to determine students' AQ intelligence. The results of the research on the mathematical creative thinking ability test showed that there were no students who could meet the novelty indicators, so that level 1 (Very Creative) mathematical creative thinking skills were not fulfilled. From the AQ questionnaire given to 12 students containing the CORE dimension, it was obtained a group of students with high AQ intelligence or it could be called the climber category group. In the climber category there are 2 people (17%). Students in the moderate AQ intelligence group or what could be called the camper category group numbered 10 people (83%). Meanwhile, students in the low AQ intelligence group or the quitter category group were not found in this study. This shows that there are no students who avoid assignments or who immediately give up without trying first. Keywords: Creative Thinking Skill, Adversity Quotient, and area of plane shapes.